Intelligent elderly care - Soon, Gerald Wei Sheng (Nanyang Technological University, 2022)
With the increasing ageing population around the world and elderlies living independently, there is a need for remote monitoring and alert system for the elderly with Dementia. It has been predicted that the number of people aged 60 and over will suffer from Dementia and will continue to rise significantly. Thus, there is a need to find innovative technological devices to assist caregivers who might not be living with the elderly. Furthermore, family members often restrict these elderly from leaving the house to prevent them from getting lost or injured. However, this imposes a greater issue on their mental health and may even lead to depression. Thus, this project aims to create an intelligent GPS tracking and monitoring system with other features such as a fall detector and a camera function which can be controlled remotely via Telegram Bot. The Intelligent Elderly Care hopes to improve the lives of these Dementia elderlies by using innovative technologies available.